AUDITOR SWITCHING: OPINI AUDIT, PERGANTIAN MANAJEMEN, DAN AUDIT FEE - Fadhila Rahardiani (2023)
This study aims to determine the effect of audit opinion, management turnover, and audit fee on auditor switching in the non-financial companies sector for the 2019- 2021 accounting period. This research is a quantitative research that uses secondary data in the form of financial reports obtained from the official website of the Indonesia Stock Exchange (IDX) and the company's official website. This study used a sample of 250 companies and 750 total research datas. The technique for analyzing the data in this study uses logistic regression analysis. This study uses the STATA 14.1 application and by the assistance of Microsoft Excel. Based on the results of the tests that have been carried out, it shows that audit opinion and management turnover do not have a significant effect on auditor switching. Then the audit fee has a negative effect on auditor switching.